"Forms Not Formula" or: Doing Justice to Poetry (KULT_online, 2009)
This collection of articles on 'new poetry' is impressive for well-substantiated analyses which successfully combine secondary scientific examinations with a broad bibliography, as well as for diverse content which ranges from an interview with the influential poet Heinz Czechowski to recent work by highly contemporary authors. Contemporary or 'new' German poetry is thereby not equated with the controversially labeled 'poets of now' (referring to the title Lyrik von Jetzt, edited by Björn Kuhligk and Jan Wagner), but rather embraces authors of different generations and different German-speaking countries. The assembled contributions cover lyric works since the nineties and therefore do not aim for a comprehensive overview, but rather a highlighting of various approaches to different topics as well as forms, patterns and individual styles of contemporary German poetry.